The Importance of Adaptive Sports in The Socialization of People with Disabilities - Lilia Tabrisovna Seidalieva (Bright Mind Publishing, 2025)
The article deals with the actual problem of the place of sports in the processes of socialization of the personality of people with disabilities.
Keywords: Adaptive sports, Paralympic sports, society, communication, quality of life, discipline, adaptation.